Preparation and Investigation of the SPF and Antioxidant Properties of O/W and W/O Emulsions Containing Vitamins A, C and E for Cosmetic Applications - Nikolaos D. Bikiaris; Ioanna Koumentakou; Katerina Hatzistamatiou; Smaro Lykidou; Panagiotis Barmpalexis; Nikolaos Nikolaidis (Cosmetics, 2023)
In the current work, Oil in Water (O/W) and Water in Oil (W/O) emulsions containing Vitamins A, C and E in 0.5, 1 and 2% wt concentrations were prepared. The pH and viscosity stability over storage, as well as the sunscreen and antioxidant properties of the obtained emulsions, were investigated. The results obtained showed that vitamins slightly increased the pH of the blank emulsions; however, their pH values were within the acceptable values (pH = 4–6). Nevertheless, all emulsions presented excellent pH stability during storage for up to 90 days. Similar results were observed by rheological measurements as the prepared emulsions did not exhibit viscosity instabilities deriving during storage. Moreover, emulsions containing Vitamin A exhibited higher UV protection than the other emulsions, as the W/O emulsion containing 2% wt Vitamin A presented the highest SPF value at 22.6.